ANALISIS PENERAPAN APLIKASI SITAB UNTUK MEWUJUDKAN EFEKTIVITAS PELAPORAN PERTANGGUNGJAWABAN ANGGARAN PEMILU 2024 OLEH PPK DI KABUPATEN PONOROGO - Silfia, Ana; Firdausi Mustoffa, Ardyan (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Today's developments are increasingly advanced, one of the impacts is technological progress. The technology created is of course to make work easier, such as reporting budget accountability for general elections which previously was still manual, now when the 2024 general election applies the SITAB application for reporting. This research was conducted to see the effectiveness of implementing SITAB for PPK budget accountability reporting in Ponorogo Regency. Researchers used a qualitative descriptive approach method with data sources coming from primary data and secondary data. Researchers collect data through observation, interviews and documentation techniques, where the data analysis technique refers to the Miles and Huberman model, namely the data reduction stage, data presentation stage and conclusion drawing or verification stage.